Meningkatkan Efisiensi Skema Irigasi Cascade di Daerah Irigasi Tampo, Sumatera Barat - Elvi Roza Syofyan; Revalin Herdianto - (Jurnal Ilmiah Poli Rekayasa, 2017)
Current water use practice in Tampo Irrigation District is thought as inefficient, since water from main canal is drained to neighboring stream without further use by downstream farms. The remaining paddy farm receives less water from the same source canal. As the result the farms could only harvest once per year. A new irrigation scheme is proposed by diverting water back to the main canal to be used by farms downstream the canal. The proposed method is by using DEM and GIS information, coupled with computation of current water use of the existing farms.The study is begun by identifying the existing farms in topography, irrigation networks, and water use. We use 30 m DEM by ASTER GDEM, coupled with Google Earth to identify stream networks and to delineate basin. The results are confirmed with field measurement in which elevation of structures such as weir, gates, hubs are recorded using GPS. Pertinent points in the field are also recorded by GPS. The existing farms are delineated and marked. Water flow rate are measured in the field using traditional method.We found that the existing water use is insufficient to irrigate the irrigation district. Instead of improving efficiency of the irrigation scheme, water needs additional supply by various means.Otherwise crops cannot be increased more than once a year. We identified another potential water source near the irrigation network that can be directly connected to the existing network. This could irrigate another 100 hectares land.